PENGARUH NILAI TUKAR, SUKU BUNGA KREDIT DAN INFLASI TERHADAP ALIRAN MODAL JANGKA PENDEK DI INDONESIA (Studi Kasus Tahun 2000-2015) - Siregar, Rifqah Pratiwi; Mayes, Anthony; ', B. Isyandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in Indonesia. The purpose of this study was to determine the effect of exchange rates, lending rates and inflation on short-term capital flows (portfolio investment) and to know which variable is more dominant influence on short-term capital flows (portfolio investment). This study uses time series data over the period 2000-2015, which is a secondary data obtained from Bank Indonesia Riau Province, the Central Statistics Agency of Riau Province. Data were processed using SPSS 2.10 analytical tools using multiple linear regression analysis with OLS (Ordinary Least Square). Further statistical tests on the study include F-test, t-test, and R2 (coefficient of determination) as well as the classical assumption test. The results of data analysis using OLS (Ordinary Least Square) shows that the exchange rate positive and significant impact on the flow of short-term capital (portfolio investment) in Indonesia, mortgage interest rates have a negative and significant impact on the flow of short-term capital (portfolio investment) in Indonesia, while inflation has and no significant negative influence on short-term capital flows (portfolio investment) in Indonesia. Tests on the classical assumption that the model results of research obtained free of symptoms of normality, multicollinearity,autocorrelation, andheterokedastisitas.Keywords: Exchange Rate, Interest Rates, Inflation and Portfolio Investment